Alcohol use among in-school adolescents in Sierra Leone - Bright Opoku Ahinkorah; Abdul-Aziz Seidu; Peter Bai James; Richard Gyan Aboagye; Augustus Osborne; Comfort Z Olorunsaiye; Camilla Bangura; Jia B Kangbai (BMJ Open, 2024)
Objective To examine the prevalence of alcohol use and its associated factors among in-school adolescents in Sierra Leone.Design Data for the study was sourced from the 2017 Sierra Leone Global School-Based Student Health Survey, a nationally representative survey conducted among in-school adolescents aged 10–19 years using a multistage sampling methodology. Percentages were used to present the prevalence of alcohol use among in-school adolescents. Multivariable binary logistic regression analysis was performed to examine the factors associated with alcohol use among in-school adolescents. The results were presented using adjusted odds ratios (aOR) with their respective 95% confidence interval (CI).Setting Sierra Leone.Participants A weighted sample of 1730 in-school adolescents in Sierra Leone.Outcome measure Current alcohol use.Results The prevalence of alcohol use among in-school adolescents was 10.7% (7.3, 15.3). In-school adolescents in senior secondary schools were more likely to use alcohol compared with those in junior secondary school (aOR=2.13; 95% CI 1.37, 3.30). The odds of alcohol use was higher among in-school adolescents who were truant at school relative to those who were not (aOR=2.24; 95% CI 1.54, 3.26). Also, in-school adolescents who were bullied (aOR=1.85; 95% CI 1.24, 2.76), ever engaged in sexual intercourse (aOR=2.06; 95% CI 1.39, 3.06), and used marijuana (aOR=3.36; 95% CI 1.72, 6.53) were more likely to use alcohol compared with those who were not. However, in-school adolescents who reported that their parents understood their problems (aOR=0.52; 95% CI 0.33, 0.82) had a lower likelihood of consuming alcohol.Conclusion Our study has shown that alcohol use is prevalent among in-school adolescents in Sierra Leone. Grade level, experiences of being bullied, history of sexual intercourse, truancy at school, and previous use of marijuana were the factors influencing alcohol use among in-school adolescents. The findings emphasise the necessity of creating school-based health interventions in Sierra Leone that can effectively identify in-school adolescents potentially vulnerable to alcohol-related issues. Also, existing policies and programmes aimed at reducing alcohol use among in-school adolescents need to be strengthened.